EVALUATION OF THE MODEL OF EDUCATION IN ISLAMIC ECONOMICS AND FINANCE: Empirical Evidences From Indonesia and United Kingdom - Euis Amalia (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2014)
This study attempts to evaluate the model of education in Islamic economics and finance that currently adopted in Indonesia and United Kingdom. The study employs the method of Analytic Network Process (ANP). This study decomposes the problem by way of undertaking in-depth interviews and questionnaires as preliminary steps to all stakes holders in these countries comprising practitioners, academicians, experts and users. In order to evaluate and measure these differences, pair-wise comparison is conducted followed by synthesis method to come up with appropriate solutions. The root of the problem comprises of internal and external, while the solution includes short term as well as long terms with strategic policy as the last outcome. The finding of this study demonstrates different results in every cluster of respective countries. Moreover, the findings reveal that quite a few challenges lie ahead in applying the best model to be used as teaching materials in these countries.